NFL Football : A History of America's New National Pastime - Crepeau, Richard C., 1941- (Book collections on Project MUSE., 2014)
"The National Football League was founded in 1920 as the American Football Association. At first is struggled in the shadow of baseball as a vaguely disreputable professional sport, and had trouble competing for athletes and fans. Through a series of mergers, moves between cities, and the advent of television, the NFL gradually grew into one of the nation's most successful professional sports, with cities competing for franchises, and networks competing for broadcast rights. Its stars became national celebrities and its championship game became an annual extravaganza. The highly respected sports historian Richard Crepeau will write a history of the NFL from its hardluck origins to its current glory. He will deal not only with the great teams, great games, and great rivalries, but also with the place of NFL within American culture"--